ANALISIS RISIKO PADA PEKERJAAN DOKTER GIGI DI KABUPATEN DAN KOTA PROBOLINGGO - Mia Rhosita Sawitri; Mulyono Mulyono (Universitas Airlangga, 2019)
This research is aimed to hazard identification, risk assessment, risk control, and risk residual on dentist's job in Probolinggo. This kind of research is observational research by using descriptive method with cross sectional design. The population of this research including dentists in Probolinggo as much as 70 dentists that included in Persatuan Dokter Gigi Indonesia (PDGI) Probolinggo. The sampling of this research is being done by using simple random sampling method. The sample in this research is 41 people. This research is conducted in Probolinggo. The instrument used is task risk assessment sheet, Baseline Risk Identification of Ergonomics Factors (BRIEF) observation sheet, questionaire, sound level meter, and lux meter. Based on the result of this research, it is known that the job of dentist has 12 potential of danger and 8 risks. Risk assessment in the job of dentist has 3 low risk categories, 7 medium risk categories, and 2 high risk categories. As the conclusion of this research shows that the job of dentist have not applied risk control of ergonomics hazard yet. The suggestion for the respondent is by doing stretching move either in the break time or when doing the action and take a chance to do physical activity such as doing sport regularly.Keywords: hazard identification, risk assessment, risk controlling